The Relationship Between Emotional Control with Sleep Quality in Elderly with Hypertension: The Relationship Between Emotional Control with Sleep Quality in Elderly with Hypertension - Junianto Fitriyadi (Journal of Nursing Periodic, 2026)
Introduction: Hypertensive elderly with emotional instability can result in reduced effective sleep time, thus disrupting adequate sleep quality and leading to various sleep complaints. The purpose of this study was to determine the relationship between emotional control with sleep quality in hypertensive elderly. Methods: The researchers used a cross-sectional study design. The population was elderly hypertensive patients who came for check-ups at the Bendo Community Health Center in Pare District. A sample of 35 elderly hypertensive patients was selected using an accidental sampling technique. The research instruments used were the Emotion Regulation Questionnaire (ERQ) and the Pittsburgh Sleep Quality Index (PSQI). The Spearman Rho statistical test was used for analysis with a margin of error of 0,05. Results: Almost half of the respondents had emotional control in the very low category as many as 17 respondents (48,6%) and most respondents had sleep quality in the poor category as many as 19 respondents (54,3%). Spearman correlation test analysis obtained a Sig.2-tailed value of 0,002 which indicates a relationship between emotional control and sleep quality in elderly hypertensives, while the correlation coefficient value of 0,504 with the strength of the relationship is included in the moderate category and is positive which means that if emotional control in elderly hypertensives is very low it will have poor sleep quality. Conclusions: Elderly people with hypertension can control their emotions by providing adaptive responses in dealing with daily life problems and improving their spirituality to better accept the condition of their illness, as well as maintaining an effective sleep pattern to restore their physical condition to stay healthy.